Sulfur microenvironments as hotspots for biogenic pyrite formation - Fatih Sekerci; Stefan Fischer; Prachi Joshi; Stefan Peiffer; Andreas Kappler; Muammar Mansor (Scientific Reports)
Abstract Pyrite (FeS2) is the end-product of bacterial sulfur cycling in reduced sedimentary environments. Sulfate-reducing bacteria (SRB) are mostly considered for biogenic pyrite formation due to their significant contribution to sulfide production at ambient temperatures. However, most experiments using SRB for biogenic pyrite formation resulted in the formation of only metastable iron sulfide minerals such as mackinawite (FeS). In this study, we investigated the roles of elemental sulfur (S0) and microbial sulfur reduction for pyrite formation. To this end, we cultivated the Fe(III)- and sulfur-reducing bacterium Geobacter sulfurreducens in the presence of the Fe(III) (oxyhydr)oxide mineral ferrihydrite and elemental sulfur at two different Fe/S ratios (4:1 and 1:4). While only mackinawite formed in Fe/S: 4:1 experiments, sulfidic conditions in the Fe/S: 1:4 experiments favored greigite (Fe3S4) and pyrite formation via the polysulfide pathway. Morphological observations demonstrated that spherulitic pyrite particles formed at the surface of elemental sulfur, with clusters forming that preserved the original morphology of sulfur particles. Our results showed that sulfur-reducing bacteria could replace the role of SRB as a sulfide source and further showed that sulfur particles are likely hotspots for biogenic pyrite formation by creating polysulfide-rich microenvironments and by acting as templates for spatially heterogeneous pyrite precipitation in nature.